Social representation of STD/Aids for sheltered adolescents with life experience in the streets of Goiânia - Borges, Ida K.; Medeiros, Marcelo (Brazilian Journal of Sexually Transmitted Diseases, 2004)
Introduction: adolescents in street situation likely exposed to STD/AIDS, because the street world is favorable for violence, use and traffic of drugs,sexual exploration. Objective:in this study we sough to identify and to analyze the social representations of prevention DST/Aids for a group of ado-lescents with experience of life in the streets, living in a shelter institution in Goiânia, Brazil. Methods:this inquiry has been based on socialapproach of qualitative research in health. The data was collected by in-depth interview with a group of sheltered adolescents of both genres anddiary-field notes from participant observations, and analyzed by thematic modality of the content analysis. Results:as results we identified three the-matic categories: “omnipotence and finite”, prevention and risks, bodies changes, in order to we verify that aids is better known among them thanother STD. In their understanding Aids appears as incurable disease leading to death. Although they know about risks they do not adopt a preventionbehavior. The risk factors are linked to their own powerful beliefs, ignorance, use of inject able drugs or others and difficulties to get condoms makesthat diminishes the risks perceptions threshold and, consequently, also their protection attitudes. The knowledge about sexuality is restricted to thephysical and biological modifications, not knowing exactly what is happening with their body, in each phase of their physical, affective, sexual andsocial development. Considering the irregularity that initiates their sexual life time, some limitations to preventing their selves against STD appears.Conclusion:these results allow us to consider about our responsibility to extending our activities beyond the limits of Academy and thus, contribu-ting to Public Policy elaboration through accords with governmental and non-governmental organizations, by a community effort to propose effectiveprojects of interventions for this population, still unknown for great part of the society, inside of its historical context.